DETERMINASI TINGKAT SUKU BUNGA DASAR KREDIT MIKRO (STUDI KASUS PADA BANK BUMN DAN BANK UMUM SWASTA NASIONAL DI INDONESIA PERIODE MARET 2013 – OKTOBER 2014) - Indah Sulistyawati; Ajeng Kartika Galuh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aims to find out the effect of cost of loanable fund, overhead cost, MSME’s risk and loan to deposite ratio on micro base lending rate in state owned bank and foreign exchange commercial bank. Panel data regression is used to analyze this data research. Using this method, it can be analyzed the impact of factors which are determines micro base lending rate in fixed effect model. The results of this research are only MSME’s risk is determining micro base lending rate in state owned bank and foreign exchange commercial bank’s micro base lending rate is determined by overhead cost, MSME’s risk and loan to deposite ratio. Keyword: Micro Base Lending Rate, Cost of Loanable Fund, Overhead Cost, MSME’s risk, Loan to Deposite Ratiio, Panel Data Regression.